Bio-Chemical Changes in Women During Normal and Menstruation Periods - Mangayarkarasi, S. (Asian Journal of Chemistry, 2010)
There are many common misconceptions associated with women actively involved in various strenuous activities as well as participating in sports activities during menstruation. Many findings show that for the majority of young athletes. Physical performance itself is not materially affected by the menstrual period. The biochemical changes which take place during the phase of the cycle in women is being discussed